Parental factors as determinants of social inclusion of students with hearing impairment in Ibadan, Oyo State, Nigeria (2013)
The study examined parental factors as determinants of social inclusion of students with hearing impairment in Oyo State, Nigeria. Descriptive survey design of the correlational type was adopted for the study. Purposive sampling technique was used to select 60parents of students with hearing impairment in Ibadan. One research instrument was used for data collection: parental factors and social inclusion questionnaire (r=0.83). Three research questions were generated and answered in the study. Data were analysed using Pearson Product Moment Correlation and multiple regression analysis. The study found that parents' marital status (r=0.782, <0.05), parenting style (r=0.539, <0.05) and socio-economic status (r=0.865, <0.05) correlated with social inclusion of students with hearing impairment. The findings of the study also showed that parents' marital status, parent socio- economic status and parenting style significantly predicted social inclusion of students with hearing impairment (F- ratio of 64.045p<0.05.). The relative contributions of the independent variables to the dependent variable are as follows: parent socio-economic status (β=0.851), parent marital status (β =0.184), parenting style (β =0.158) respectively. It was therefore, recommended that parents should play key roles in ensuring the inclusion of their children with hearing impairment into the mainstream of the society.